Pathologic Periprosthetic Fracture After Radial Head Arthroplasty: A Report of 2 Cases. Issue 3 (13th July 2022) - Ozdag, Yagiz; Foster, Brian; Grandizio, Louis C.
Abstract : Case: We present 2 cases of pathologic periprosthetic radius fractures in the setting of osteolysis after radial head arthroplasty (RHA) with a porous-coated, press-fit implant. Both patients were managed with implant removal without subsequent instability. Although radiographic lucencies are common after RHA, progressive bone resorption can result in subsequent periprosthetic fractures. Conclusion: Although osteolysis after RHA is not always clinically significant, these cases demonstrate that this radiographic finding may indicate adverse clinical consequences. Surgeons who perform implant excision should be ready to address further instability as needed. Level of Evidence: Level V, case reports.